Does the Geohealth domain require a body of knowledge? - Ellen-Wien Augustijn-Beckers; Sherif Amer; Rob Lemmens; Robert Bergquist (Geospatial Health, 2022)
To answer the question if the Geohealth domain requires a body of knowledge (BoK), we need a general understanding of concepts associated with this field. Two years ago, the United Nation (UN) committee of experts on global geospatial information management identified “semantic- and ontology-linked data” as something that “will become essential to support the next generation of autonomous systems” (UN-GGIM, 2020). The term ontology is closely related to BoK. Unlike data models, ontologies are independent of application; they are generic, can be used in different ways and have clear advantages but they are challenging to create and even more difficult to maintain.